2019
DOI: 10.1117/1.jbo.24.12.128002
|View full text |Cite
|
Sign up to set email alerts
|

Strong bonding of corneal incisions using a noncontact fiber-optic laser soldering method

Abstract: Suturing of corneal incisions requires significant skill. We demonstrate a noncontact method that will simplify the bonding process. 5-mm-long penetrating vertical and slanted incisions were made in corneas of eyes, extracted from dead piglets. A fiber-optic laser system was used for laser soldering of the incisions, under close temperature control, using albumin solder. The burst-pressure P B immediately after the soldering was found to be P B ≈ 92 and 875 mmHg, for vertical and slanted incisions, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…Other methods, not laser-coupled, were an IR camera recording the surface temperature [ 36 , 47 ] and a thermocouple, either beneath the tissue [ 38 ] or between the tissue and the solder [ 43 , 44 , 53 , 56 ]. This temperature range is consistent with published data of laser tissue soldering of other tissues as well [ 6 , [66] , [67] , [68] ]. One study, Rabi et al, 2010 [ 59 ], demonstrated increasing bond strength with a series of rising temperatures up to 150 °C.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other methods, not laser-coupled, were an IR camera recording the surface temperature [ 36 , 47 ] and a thermocouple, either beneath the tissue [ 38 ] or between the tissue and the solder [ 43 , 44 , 53 , 56 ]. This temperature range is consistent with published data of laser tissue soldering of other tissues as well [ 6 , [66] , [67] , [68] ]. One study, Rabi et al, 2010 [ 59 ], demonstrated increasing bond strength with a series of rising temperatures up to 150 °C.…”
Section: Discussionsupporting
confidence: 92%
“…Laser technology has been used as an alternative method for tissue bonding in different tissues, with recent-years studies on skin [ 5 ], cornea [ 6 ], oral mucosa [ 7 ], and even nerves [ 8 ]. Laser tissue bonding through thermal reaction can be performed by 2 main methods: Laser Tissue Welding (LTW) in which a laser diode is used to heat the tissue edges; and Laser Tissue Soldering (LTS) in which the bond is generated through the heating of a dedicated proteinaceous solder material.…”
Section: Introductionmentioning
confidence: 99%
“…[67] Others have developed elegant infraredbased CO 2 lasers for tissue soldering. [68][69][70] Combining tissue soldering technology with CaproGlu may open more avenues of application for tissue fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The regenerative process of an injury depends on coordination of four stages (Fung et al 1999;Islam et al 2014;Ruprai 2019) i.e. hemostasis and coagulation stage (Gomes et al 2019) in which clotting of blood occurs to minimize blood loss (Wang et al 2019;Unsihuay et al 2021), inflammatory stage starts inflammatory reactions and removes the waste of dead cells (Feng et al 2020;Wang et al 2020;Lee et al 2022), proliferatory stage initiates within few days of wound and involves reconstruction of connective tissues, starts production of denovo network of circulatory system and construction of epithelium (Redmond and Kochevar 2019;Narayanan et al 2020;Noori-Dokht et al 2022;Yelkuvan et al 2023) and maturation phase (Yan et al 2022) which causes refurbishing of collagen form III to form I (Basov et al 2019; Fuentes-Lemus and Lopez-Alarcon Li et al 2021;Liu et al 2022;Liang et al 2023). Maturation phase involves the formation of scar and may last up to a year or more (Sarabi et al 2021;Wanasingha et al 2021;Klelemen et al 2022;Lee et al 2023).…”
Section: Introductionmentioning
confidence: 99%